The Influence of Net Profit Margin and Return on Equity on Profit Growth at PT Indo Tambang Raya Megah Tbk 2010-2023 (Case Study of Mining Companies Listed on the Indonesia Stock Exchange) - Siti Nur Fauzia (Formosa Journal of Social Sciences (FJSS), 2024)
The purpose of this study is to analyze the financial data of PT Indo Tambangraya Megah Tbk from 2010 to 2023 to determine the impact of net profit margin and return on equity on profit growth. A descriptive associative approach is used for this study. The selection process is based on predetermined criteria, including the annual financial statements of PT, and is carried out using a non-probability sampling methodology using a special sampling method. Tambangraya Megah, Tbk 2010–2023 We use multiple linear regressions, t-tests, F-tests, coefficients of determination, and Pearson product-moment correlation analysis to verify our hypotheses about the impact. The study shows that both Net Profit Margin and Return On Equity values ​​for profit growth are in the strong range, falling at 0.666 and 0.643, respectively, indicating strong profitability. The results of the determination analysis reveal that other factors account for 55.4% of the variance in Profit Growth, while the independent variables (Net Profit Margin and Return On Equity) contribute 44.6%